Educational concussion module for professional footballers: from systematic development to feasibility and effect - Gouttebarge, Vincent (BMJ Open Sport Exerc Med, 2019)
OBJECTIVES: To describe: (1) how we developed a concussion module and (2) whether the concussion module is feasible (in terms of relevance, added value and suitability) and enhances knowledge and changes attitude of professional footballers about concussion. DEVELOPING THE CONCUSSION MODULE: We developed the concussion module based on two structured and systematic processes. First, our needs assessment (questionnaire and interviews) in professional football (especially players) revealed that a 5–10 min concussion module was needed, ideally disseminated during club visits. Second, the objectives were defined (from published literature and by experts) as to disseminate essential information about what concussion is (definition), how to recognise it and the importance of removing a player with (suspected) concussion from the football field. We included an introductory video featuring a high-profile professional footballer and an animated educational component on defining concussion, recognising it and removing affected players from the field. FEASIBILITY AND EFFECT: A quasiexperimental study (pretest post-test design) was conducted among 61 professional footballers. These players were asked to complete two questionnaires related to knowledge about and attitude towards concussion and feasibility of the module: one before and one after viewing the concussion module. Potential increase in knowledge and attitude was explored by comparing the pretest and post-test scores of the Rosenbaum Concussion Knowledge and Attitudes Survey with the non-parametric Wilcoxon signed-rank test (p<0.05). The mean knowledge score of the participants was stable between tests (Z=213; p=0.16), while mean attitude score increased significantly (Z=331; p=0.01). Nearly all participants (85%–100%) were positive about the relevance, added value, duration and form of the concussion module. CONCLUSION: The developed educational concussion module leads to better attitude of professional footballers towards concussion.